Analysis of Smoking Behavior and Stress Management in Hypertension Sufferers of Productive Age at Dr. Moedjito Dwidjosiswoyo Hospital Jombang - Eval Braco Athatur; Sandu Siyoto; Bambang Pardjianto (Journal for Quality in Public Health, 2021)
The high incidence of hypertension is caused by various causes including the lifestyle of the city community such as obesity, excessive salt consumption, lack of exercise, smoking. In addition, a person's lifestyle psychic condition such as stress can also affect the increase in blood pressure. Stress increases the activity of sympathetic nerves, thus raising blood pressure erratically. The purpose of the study was to analyze smoking behavior and stress management of hypertension sufferers of productive age. The design of this research is analytics with a crossectional approach. The variables of this study are smoking behavior and stress management as independent variables as well as blood pressure as dependent variables. The study population of patients with hypertension hospital dr. Moerdjito Jombang as many as 142 patients in March 2020. Samples were taken with simple random sampling techniques as many as 105 respondents. The data was collected by questionnaire instrument and processed using editing, coding, scoring and tabulating and tested with spearman rho test. This suggests that smoking behavior and stress management in sufferers may affect